2022
DOI: 10.3389/fvets.2022.1056996
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-based detection and typing procedures for Burkholderia mallei: Assessment and prospects

Abstract: Although glanders has been eradicated in most of the developed world, the disease still persists in various countries such as Brazil, India, Pakistan, Bangladesh, Nepal, Iran, Bahrain, UAE and Turkey. It is one of the notifiable diseases listed by the World Organization for Animal Health. Occurrence of glanders imposes restriction on equestrian events and restricts equine movement, thus causing economic losses to equine industry. The genetic diversity and global distribution of the causing agent, Burkholderia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 83 publications
(150 reference statements)
1
1
0
Order By: Relevance
“…Other Chinese isolates, such as strain China 5 and ATCC 10399, were found in L5. Interestingly, strains FDAARGOS_587, 2000031063, and KC_1092 were also clustered in L5, an observation which is consistent with previous publications that have pointed out inaccurate metadata for these isolates ( 15 , 54 , 55 ). The majority of isolates from Turkey were grouped into L2.…”
Section: Resultssupporting
confidence: 90%
“…Other Chinese isolates, such as strain China 5 and ATCC 10399, were found in L5. Interestingly, strains FDAARGOS_587, 2000031063, and KC_1092 were also clustered in L5, an observation which is consistent with previous publications that have pointed out inaccurate metadata for these isolates ( 15 , 54 , 55 ). The majority of isolates from Turkey were grouped into L2.…”
Section: Resultssupporting
confidence: 90%
“…The fliP pseudogene is described as incomplete, which agrees with a potential disruption caused by an insertion sequence. The genome size can also be used to distinguish B. mallei from B. pseudomallei; B. mallei has a smaller genome size than B. pseudomallei (~7.2 Mb) [32]. Accordingly, B. mallei BAC 86/19 showed an estimated genome size of 5.51 Mb, which is in accordance with other B. mallei strains and smaller than that of B. pseudomallei [32].…”
Section: Discussionsupporting
confidence: 58%
“…The differentiation of B. mallei from B. pseudomallei has been historically difficult due to their high genomic similarity [32]. A major phenotypic difference between the two species is motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The report by Limmathurotsakul et al showed that diabetes is an important risk factor for Burkholderia pseudomallei infection. The report by Syed et al pointed out that the prevalence of Burkholderia pseudomallei infection is increasing ( Limmathurotsakul et al, 2016 ; Syed and Wooten, 2021 ; Brangsch et al, 2022 ). Brucella spp.…”
Section: Discussionmentioning
confidence: 99%